Luxury purchase intentions: the role of individualism-collectivism, personal values and value-expressive influence in South Africa - Ayanda Zici (Taylor & Francis Group, 2021)
This study examines the underlying mechanisms for predicting luxury purchase intentions in the context of an emerging market. The authors propose a conceptual model that tests the predictive role of culture and the mediating effect of individual values and value-expressiveness to explain luxury purchase intentions. To determine the antecedents of luxury brand purchase decisions, a survey of South African luxury consumers was carried out. Based on the hierarchy-of-effect model of values, this study supports the notion that higher-order cultural values—individualism and collectivism have predictive influence on individual-level values, self-enhancement, and materialism, which in turn, affect luxury brands’ value-expressiveness to predict luxury purchase intentions. The study results also reveal that luxury brands’ image interacts with value-expressiveness to explain luxury purchase intentions. Also confirmed was the direct effect of individualism and luxury purchases, whereas collectivism was not confirmed.